2008
DOI: 10.1016/j.expneurol.2008.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of morphine is associated with a decrease in surface AMPA GluR1 receptor subunit in dopamine D1 receptor expressing neurons in the shell and non-D1 receptor expressing neurons in the core of the rat nucleus accumbens

Abstract: The nucleus accumbens (Acb) is an extensively studied neuroanatomical substrate of opiate reward and the neural plasticity associated with chronic opioid use. The cellular mechanisms mediating opioid-dependent plasticity are uncertain, however AMPA-type glutamate receptor trafficking in dopamine D1 dopamine receptor (D1R) expressing neurons may be a potential cellular pathway for these adaptations, although there is no evidence for this possibility. Immunogold electron microscopy was used to quantify the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 52 publications
2
33
0
Order By: Relevance
“…Microinjection of ionotropic glutamate receptor antagonists MK-801 or DNQX into the VTA attenuated the reinforcement effect in heroin addiction (Xi and Stein, 2002b). Chronic intermittent injection of escalating doses of morphine is accompanied by ultrastructural plasticity of GluR1 in neurons that are responsive to glutamate, activation of DA-induced D1 dopamine receptor in the NAc shell, and activation of neurons capable of responding to glutamate but not to D1 dopamine receptor stimulation in the NAc core (Glass et al, 2008). These results indicate that glutamate released in the central nervous system plays an important role in opioid withdrawal behaviors and that the iGluRs are involved in the process.…”
Section: The Role Of Glutamate and Its Receptor In Opioid Addictionmentioning
confidence: 99%
“…Microinjection of ionotropic glutamate receptor antagonists MK-801 or DNQX into the VTA attenuated the reinforcement effect in heroin addiction (Xi and Stein, 2002b). Chronic intermittent injection of escalating doses of morphine is accompanied by ultrastructural plasticity of GluR1 in neurons that are responsive to glutamate, activation of DA-induced D1 dopamine receptor in the NAc shell, and activation of neurons capable of responding to glutamate but not to D1 dopamine receptor stimulation in the NAc core (Glass et al, 2008). These results indicate that glutamate released in the central nervous system plays an important role in opioid withdrawal behaviors and that the iGluRs are involved in the process.…”
Section: The Role Of Glutamate and Its Receptor In Opioid Addictionmentioning
confidence: 99%
“…It has been reported that chronic morphine treatment can cause functional changes in dopamine-containing neurons that spread widely within these regions and results in an increase in neuronal activity and dopamine release from their nerve terminals (Berridge and Robinson, 1998;Spanagel and Weiss, 1999;Schultz, 2000). In addition, morphine-induced adaptive changes in postsynaptic parts of dopaminergic projections in NAc and PFC also have been reported (Ito et al, 2007;Glass et al, 2008;Narita et al, 2010). However, little is known about adaptive changes in dopaminergic signaling in BLA upon chronic morphine treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a single dose of morphine increases synaptic strength at excitatory synapses in the ventral tegmental area (VTA; Saal et al, 2003) and produces a delayed increase in glutamate receptor responses in the nucleus accumbens (NAc; Jacobs et al, 2005). Furthermore, repeated morphine administration induces structural changes in dendritic processes in NAc and prefrontal cortex (PFC; Robinson and Kolb, 1999), as well as changes in the level of expression and subcellular localization of GluR1 receptors (Fitzgerald et al, 1996;Glass et al, 2005Glass et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%